iINVENT pathways and practices: prizing the process over the product - Rowe, Susan R. M.; Talamantes, Adam; Well, Jay; O'Neill, Renee; Nicholson, Emily; Rowe, Shawn (Frontiers in Education, 2024)
Rural communities need skilled innovators who engage as community members, support economic opportunities, and develop novel ways to solve local problems. Through innovation, Invention Education (IvE) is one way to promote the creativity and problem-solving needed to restore economic vitality to regions of the rural US. IvE pathways support a skilled workforce that communities can draw upon to solve complex problems. Introductory IvE experiences can begin to bolster rural recovery and open prime grounds for innovative solutions. The Office of Precollege Programs at Oregon State University established the iINVENT Program for upper elementary, middle, and high school learners to engage in IvE and act as inventors. In this study, we describe the iINVENT pathways resulting from 8 years of curriculum design and iteration guided by engaged scholarship practices and robust evaluation. Program data from 2019–2023 was collected via learner, educator, community partner, and parent surveys, as well as through observations conducted by program staff and partner instructors. Results from qualitative content and thematic analysis demonstrate the value of introducing learners to IvE and how iINVENT practices support invention educators in impacting youth learners. The findings demonstrate essential practices, successes, and challenges that have shaped the iINVENT pathways and IvE curriculum delivered. Based on these findings and current discourse unfolding throughout the IvE professional community, the authors suggest that a process-oriented invention framework focused on inventiveness and the ways learners can act as inventors is pivotal to broaden access and participation in IvE, providing learners with a more applicable and relatable learning experience to cultivate inventiveness mindsets and skills transferable to all parts of life.